INTEGRATING RELIGIOSITY VALUES INTO PROJECT-BASED LEARNING: EFFECTS ON ELEMENTARY STUDENTS’ RELIGIOUS ATTITUDES : Mengintegrasikan Nilai-Nilai Religiusitas ke dalam Pembelajaran Berbasis Proyek: Dampak terhadap Sikap Keagamaan Siswa Sekolah Dasar - Nur Fajriah Safitri; Muhlasin Amrullah; Khizanatul Hikmah (SOSIOEDUKASI, 2026)
Strengthening religious attitudes among elementary school students is an important necessity amid globalization, while learning in schools still often focuses on cognitive aspects. One effort that can be made is the application of the Project Based Learning model integrated with religious values in Pancasila Education. This study aims to analyze the effect of implementing a Project-Based Learning model with religious values on the religious attitudes of fourth-grade elementary school students. This study used a quantitative approach with a one-group pretest-posttest pre-experimental design. The research subjects included all 25 fourth-grade students at SDN Candipari 2. Data processing used the Shapiro-Wilk normality test, Paired Samples T-Test, and Partial Eta Squared calculation with the help of SPSS version 25. The results of the analysis showed a significant increase in students' religious attitudes after the implementation of the Project Based Learning model, with a value of 0.000 < 0.05 and a Partial Eta Squared value of 0.869, which is classified as a large effect. These findings indicate that the implementation of Project Based Learning integrated with religious values is effective in improving the religious attitudes of elementary school students.